Pengaruh Latihan Resistance Band dan Side Plank Terhadap Akurasi Memanah Atlet Fast Malang Archery Club - Iman, Firdaus Nur; Raharjo, Slamet (STKIP Muhammadiyah Kuningan, 2025)
Archery is a sport that uses a tool to shoot a target until it hits the target. The purpose of this study was to determine the effect of resistance band and side plank training on the accuracy of archery of Fast Malang Archery Club athletes. This study used a pre-experimental design with a two group pretest-posttest design. A total of 14 athletes were divided into two experimental groups, namely the group that underwent resistance band training (7 athletes) and the group that underwent side plank training (7 athletes). Sample selection used a purposive sampling technique, with sample grouping using ordinal pairing. Measurements were made by recording the number of scores obtained by athletes in shooting arrows at targets at a distance of 30 meters. Data analysis used a paired sample test, the results in the resistance band group were 0.02 and the side plank group 0.04 <0.05, this indicates that Ha is accepted and H0 is rejected. Testing the difference in resistance band and side plank training used an independent t test with a result of 0.960 which means >0.05, there is no significant difference between the two exercises. The conclusion is that both resistance band and side plank exercise groups can improve archery scores, there is no significant difference between the two exercise groups.